Financial openness and economic growth - Norlida, Johari (2017)
In last few decades, financial openness has been widely noted around the world. The process of financial openness such as banking liberalization, trade openness, capital account liberalization has closely brought together the financial market and institutions around the world. The objective of the study is to examine the effect of financial openness on economic growth for the five major economies in ASEAN (Thailand, Singapore, Indonesia, Malaysia and Philippines) between 2000 and 2014. The balanced panel data from 2000 to 2014 for these countries has been employed in this study. The variables used are independent variable (financial openness), dependent variable (GDP) and four control variables (inflation, official exchange rate, trade and government expense). Using the Panel OLS, this study discovers a positive relationship between financial openness and economic growth. In addition, the official exchange rate and government expense are also found to influence the economic growth positively. However, the level of trade and inflation do not significantly related to economic development. For the robustness model, the FDI net inflow is employed as the independent variable to measure the financial openness. Although, different measurement of financial openness (FDI net inflows) has been used to replace the KAOPEN index, these three variables (financial openness, official exchange rate and government expense) remain to be the factors that affect the level of economic growth. In addition, supporting the earlier conclusion, inflation and trade are not influencing the economic growth. Thus, the findings provided by this study would assist the policy makers in the five ASEAN countries in assessing and strengthening the strategies on the financial openness for the benefits of the countries.